DAMPAK PENETRASI TEKNOLOGI INFORMASI DALAM TRANSFORMASI SISTEM PENYULUHAN PERTANIAN DI INDONESIA - Kadhung Prayoga (University of Jember, 2018)
The world today has entered to the era of information society connected in a virtual world. Not only in urban areas, this phenomenon is also commonly found in rural areas. Farmers in the village have begun to take advantage of their use of information technology to meet their needs. The result is a response from the government to develop an extension system based on the use of information technology called cyber extension. Based on this phenomenon, it takes a study of the effect of what is caused by the existence of cyber extension and the theory behind it. The approach used is qualitative approach using descriptive method and discourse analysis. The data used are secondary data collected through literature study method. From the discussion is known that cyber extension has given many changes in the social structure and culture of farming communities. Changes that there are moving towards the positive but there is also a precisely cyber extension causing changes to the negative direction. However, the change is not because of the reason because according to Castell, the growing information technology such as cyber extension is present in order to provide a positive effect for human life. While Bourdeau view cyber extension as an arena in which there is a fight capital owned by farmers and extension workers. So as to form a new habitus and give birth to a different social practice prior to the extension activities conducted in the virtual space. Key word: information technology, cyber extension, extension, agriculture